A Knowledge-Graph-Based Intelligent Agent for Domain-Specific Question Answering - Zhang, Mengxue; Huang, Wangwu (Translation and Linguistics (Transling), 2025)
This research focuses on the development of a question-answering intelligent agent for specialized domains based on a knowledge graph, using the field of English linguistics as an example. English linguistics encompasses a vast array of conceptual terminology and a complex knowledge structure that often lacks sufficient concrete language examples for illustration. Traditional information retrieval methods fall short in meeting the advanced demands of semantic comprehension and knowledge inference required in linguistics education. To address these challenges, this study employs Graph Retrieval-Augmented Generation (GraphRAG) technology to design and implement an intelligent agent on the Wenxin Agent Platform. This agent integrates large language models with structured knowledge graphs to enhance the performance of real-time question-answering. The knowledge graph functions as a structured repository that organizes domain-specific linguistic knowledge, thereby expanding the agent's knowledge reserve and enabling more precise responses that facilitate students' systematic understanding of linguistic concepts. Evaluation results indicate that the proposed agent surpasses general-purpose models in response accuracy and professionalism, depth and logical coherence, and explanatory transparency, while effectively addressing hallucination issues common in conventional large language models. The system demonstrates enhanced domain adaptability and improved reasoning performance within linguistic contexts.